Clinical Supervision of the Proctor Model to Improve the Ability in Conducting Nursing Care Assessment - Trigantara, Regista; Anggorowati, Anggorowati; Santoso, Agus (Universitas Airlangga, 2019)
Introduction: The function of nursing assessment is to evaluate and identify the health status of clients, thus, the nurse is required to conduct the nursing care assessment with data criteria which are complete, systematic, use a format, and which are actual and valid. The aim of this study was to understand the effect of clinical supervision of the Proctor Model against the ability in conducting nursing care assessment appropriately.Method: The type of study was quantitative research with a quasi-experimental pre-posttest control group design. The sampling method was a purposive sampling technique with 68 samples of nurse. Before and after conducting clinical supervision of the Proctor Model, the ability in conducting nursing care assessment of nurse was observed.Result: Data was analyzed by using Mann-Whitney that shows there was an effect of clinical supervision of the Proctor Model against the ability in conducting the nursing care assessment (p= 0.000).Conclussion: Normative function focused on monitoring and evaluation, formative function focused on knowledge and skill development, and restorative function focused on encouragement and motivation, thus clinical supervision of the Proctor Model could be applied as one of solution to improve the ability of nurses in conducting nursing care assessment.